PROSES PEMBUATAN PLTB HORIZONTAL - Rian Saputra, Kiki; Sunaryo, Sunaryo; Hakim, Legisnal (Manutech : Jurnal Teknologi Manufaktur, 2024)
The increase in electrical energy demand occurs due to high population growth, but this is not balanced with the increase in the supply of electrical energy, the installed power capacity remains the same, while community needs continue to increase. PLTMH (Microhydro Power Plant) and PLTB (Wind Power Plant) are power plants with renewable energy sources. This is seen from an economic and security perspective. Because currently fossil energy reserves are decreasing while the need for fuel consumption continues to increase, this has an impact on the energy crisis. PLTB has the main advantage because of its renewable nature. This means that exploitation of this energy source will not reduce wind resources like the use of fossil fuels. Based on considerations for the fulfillment of electrical energy, an economical, safe and reliable generator was built.